Cliques or Collaborators: Impressions of Cultural Collaboration in Academic Libraries - Turner, Lauren; Umana, Natalia; Solis, Denisse (Collaborative librarianship, 2023)
In 2016, Absher and Cardenas-Dow wrote that for people of color, collaboration is often "a complex social and cultural negotiation" that acts as "a coping mechanism, a way to meet every day needs, the way we succeed and thrive in an environment that is not always accepting of our viewpoints." (1) Approaching collaboration as library faculty members with an understanding of its complex nature, the authors were delighted when the opportunity to collaborate arose. All women of color, the ease at which we were able to share, create, and flow together naturally offered us all the coping that Absher and Cardenas-Dow mentioned. The impression of our newfound safety net by our white library colleagues was one of less than productive value, resulting in the labeling of us as a 'clique.' Almost picking up where Absher and Cardenas-Dow left off, we hope to examine the acts of misunderstanding and offer recommendations on how academic libraries--and many white people who work in them--can reflect on their language, intentions, and approaches to culturally exclusive collaboration. This report will touch on aspects of collaboration across departments, shifting toxic legacy practices, countering weaponized traditions of collaboration, and implementing change as new librarians.